Cultural adaptations and island ecology: Insights into changing patterns of pottery use in the Susuya, Okhotsk and Satsumon phases of the Kafukai sites, Rebun Island, Japan. (20th June 2022) - Junno, Ari; Ono, Hiroko; Hirasawa, Yu; Kato, Hirofumi; Jordan, Peter D.; Amano, Tetsuya; Isaksson, Sven
Abstract: Island chains provide access to terrestrial, coastal and offshore marine resources, attracting peoples and cultures and serving as conduits for migrations and long-distance exchange networks. Situated between Hokkaido and Sakhalin, Rebun Island connected the prehistoric cultures of northeast Asia in a major "marine highway". Rebun was repeatedly settled by distinct cultures who originated in different geographic locations and left an imprint on the local ecology. To better understand how these cultures adapted to the local island ecosystems, lipid residues from household cooking containers were investigated across a 1000-year period at the Kafukai river mouth on Eastern Rebun, where a prominent Late Holocene settlement cluster is located. Our study suggests periodical shifts in pottery function, with the Susuya focussed on the processing of intermediate trophic-level aquatic resources, and Early Okhotsk specializing towards isotopically enriched marine products. In the Middle Okhotsk phase, both marine and terrestrial animal, and plant resources were exploited. These findings elucidate changing patterns of household consumption and the range of resources processed between cultural periods. We conclude that pottery lipid analysis can play an important role in island archaeology, clarifying shifting relationships between communities, exploitation of resources and the responses of new cultural traditions to new insular ecological niches.